Developing a model for reducing maternal mortality in South Africa - Mmusi-Phetoe Rose Maureen Makapi; Masaba Brian Barasa (Sciendo, 2021)
High maternal mortality ratios (MMRs) remain a concern in many parts of the world, especially in developing countries like South Africa. Different models have been developed, tried, and tested worldwide, in the hope that they will reduce maternal mortality, but without much success.